1997
DOI: 10.1292/jvms.59.17
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Apoptotic Changes in the Gastric Glandular Epithelium of Rats Administered Intraperitoneally with Fusarenon-X.

Abstract: ABSTRACT. Fusarenon-X (FX) 1.5 mg/kg was administered intraperitoneally (ip) to 6-week-old male Wistar rats for examination of pathologic effects on the glandular stomach. Rats ip-treated with sterilized physiological saline were used as control. FX-administered rats showed dilatation of the stomach with increased fluid contents after 1-4 hr. Light microscopically, a few apoptotic karyopyknosis were seen in chief cells in the basal region at 1 hr postadministration (PA) and mitotic inhibition was evident after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
1
5
0
4
Order By: Relevance
“…By these two methods we obtained high TI and AI values after 3 hr of hydrocortisone treatment, suggesting that the activation of the death process is rapid. Li et al (1997) also verified that in rats treated with Fusarenon-X, the apoptotic peak occurred 3 hr after treatment. These results are in agreement with Grossmann et al (1998), who showed that the activation of intestinal caspases starts after a few minutes of induction and DNA fragmentation happens in 2 hr.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…By these two methods we obtained high TI and AI values after 3 hr of hydrocortisone treatment, suggesting that the activation of the death process is rapid. Li et al (1997) also verified that in rats treated with Fusarenon-X, the apoptotic peak occurred 3 hr after treatment. These results are in agreement with Grossmann et al (1998), who showed that the activation of intestinal caspases starts after a few minutes of induction and DNA fragmentation happens in 2 hr.…”
Section: Discussionsupporting
confidence: 67%
“…The differential distribution of apoptotic cells along the gastric mucosa was observed either after the TUNEL reaction or the morphological study. Li et al (1997) recorded a higher number of dead cells at the bottom of the gland, that were identified as chief cells by electron microscopy. This same study also showed that parietal cells phagocytosed the apoptotic ones.…”
Section: Discussionmentioning
confidence: 97%
“…As found for COX-2, DON can stabilize mRNAs for TNF-α (Chung et al 2003b; Chung et al 2003a) and IL-6 (Jia et al 2006) in macrophages as well as IL-2 in EL-4 T cells, (Li et al 1997a; Li et al 1997b; Li et al 1997c; Li et al 1997d; Li et al 1997e). Contrastingly, mRNA stabilization dose not play a role in DON-induced IL-8 in monocytes (Gray and Pestka, 2007, in press).…”
Section: Molecular Mechanisms For Trichothecene-mediated Immune Dysrementioning
confidence: 62%
“…By these two methods we obtained high TI and AI values after 3 hr of hydrocortisone treatment, suggesting that the activation of the death process is rapid. Li et al (1997) also verified that in rats treated with Fusarenon‐X, the apoptotic peak occurred 3 hr after treatment. These results are in agreement with Grossmann et al (1998), who showed that the activation of intestinal caspases starts after a few minutes of induction and DNA fragmentation happens in 2 hr.…”
Section: Discussionmentioning
confidence: 86%
“…The differential distribution of apoptotic cells along the gastric mucosa was observed either after the TUNEL reaction or the morphological study. Li et al (1997) recorded a higher number of dead cells at the bottom of the gland, that were identified as chief cells by electron microscopy. This same study also showed that parietal cells phagocytosed the apoptotic ones.…”
Section: Discussionmentioning
confidence: 99%